Prognostic impact of performance status on the outcomes of immune checkpoint inhibition strategies in patients with dMMR/MSI-H metastatic colorectal cancer. (September 2022) - Mazzoli, Giacomo; Cohen, Romain; Lonardi, Sara; Corti, Francesca; Elez, Elena; Fakih, Marwan; Jayachandran, Priya; Colle, Raphael; Shah, Aakash Tushar; Salati, Massimiliano; Fenocchio, Elisabetta; Salvatore, Lisa; et al.
Abstract: Background: Immune checkpoint inhibitors yielded unprecedented outcomes in patients with mismatch repair deficient/ microsatellite instability-high (dMMR/MSI-H) metastatic colorectal cancer (mCRC), but clinical decision-making in this rapidly evolving treatment landscape is challenging. Since performance status (PS) represents a well-established prognostic factor in clinical practice, we investigated whether worse PS, overall or related to either patients' frailty or high tumour burden, could affect the outcomes in this whole patients' population and according to immune checkpoint inhibitor treatment type. Methods: We conducted a global study at Tertiary Cancer Centres and collected data of patients with dMMR/MSI-H mCRC treated with anti- programmed-death (ligand)-1 (PD(L)-1) monotherapy or anti-PD-1/anti- cytotoxic T-lymphocyte antigen 4 combination. Results: The cohort included 502 patients. At a median follow-up of 31.2 months, worse PFS and OS were reported in patients with patient-related PS ≥ 1 (adjusted-HRs: 1.73, 95%CI: 1.06–2.83, p = 0.004 and 2.06, 95%CI: 1.13–3.74, p = 0.001, respectively) and cancer-related PS ≥ 1 (adjusted-HRs: 1.61, 95%CI: 1.19–2.17, p = 0.004 and 1.87, 95%CI: 1.32–2.66, p = 0.001, respectively). Anti-PD-1/anti- cytotoxic T-lymphocyte antigen 4 combination did not provide significantly better survival compared to anti-PD(L)-1 monotherapy in PS 0 subgroup (PFS HR = 0.62, 95%CI: 0.37–1.02, p = 0.059; OS HR = 0.59, 95%CI: 0.32–1.11, p = 0.100) and in patient-related PS ≥ 1 (PFS HR 0.93, 95%CI: 0.31–2.83, p = 0.899; OS HR 1.22, 95%CI: 0.34–4.37, p = 0.760), but the difference was significant and clinically meaningful in the subgroup with cancer-related PS ≥ 1 (PFS HR = 0.32, 95%CI: 0.19–0.53, p < 0.001; OS HR = 0.26, 95%CI: 0.14–0.48, p < 0.001). Conclusions: In patients with dMMR/MSI-H mCRC, an extensive evaluation of clinical variables including PS may be implemented in the therapy decision-making. Highlights: We investigated Eastern Cooperative Oncology Group performance status in 502 patients with mismatch repair deficient/ microsatellite instability-high metastatic colorectal cancer treated with immune checkpoint inhibitors. Eastern Cooperative Oncology Group performance status is independently associated with outcomes of immune checkpoint inhibitors. Programmed-death 1 blockade alone may be preferred in patients with performance status (PS) 0. Adding cytotoxic T-lymphocyte antigen 4 blockade seems not beneficial if worse PS is patient-related. Adding cytotoxic T-lymphocyte antigen 4 blockade yields meaningful benefit if worse PS is cancer-related.